Developing a checklist to inform data linkage study designs for health technology assessments: a case study linking the Cardiac Rhythm Management (CRM) register to the Secure Anonymised Information Linkage (SAIL) Databank - Ruth Louise Poole; Megan Dale; Antony Robert Wilkes; Hannah E Patrick; Mauro Lencioni; Michael Griffith; Chris P Gale; Grace Carolan-Rees (International Journal of Population Data Science, 2017)
ABSTRACT